Crystal nucleation in poly(ether ether ketone)/carbon nanotube nanocomposites at high and low supercooling of the melt. (11th June 2020) - Gohn, Anne M.; Seo, Jiho; Colby, Ralph H.; Schaake, Richard P.; Androsch, René; Rhoades, Alicyn M.
Abstract: The engineering thermoplastic poly(ether ether ketone) (PEEK) has a rigid backbone that crystallizes relatively slowly upon cooling the melt. In this study, fast scanning chip calorimetry (FSC) was used to analyze isothermal crystallization between 170 and 285 °C, a range from about 27 K above the glass transition temperature up to the melting temperature. Incorporation of carbon nanotubes (CNT) enhances nucleation at all crystallization temperatures, including low temperatures. FSC also was employed to study crystallization at cooling rates spanning 0.33 to 8000 K/s, important as PEEK is subject to these conditions during melt processing. The critical cooling rate to produce a vitrified sample was increased from 500 K/s in the neat PEEK to 4000 K/s in a 5% CNT/PEEK nanocomposite due to faster nucleation rate caused by heterogeneous nucleation. Graphical abstract: Image 1 Highlights: FSC was used to study crystallization of PEEK nanocomposites. AFM and POM were used to characterize the morphology. Low temperature crystallization shows heterogeneous nucleation. Critical cooling rate is increased with the incorporation of CNTs.